Distribuição longitudinal, dieta alimentar e ciclo reprodutivo de Pimelodella lateristriga (Osteichthyes, Siluroidei) no rio Ubatiba, Maricá, Rio de Janeiro - Porto, Luisa Maria Soares (1991)
Aspects in the longitudinal distribution, feeding habits and reproductive biology of Pimelodella lateristriga are analysed in the Ubatiba river basin (Maricá-RJ). Their distribution has been studied in nine points along the Ubatiba river basin, Pimelodella lateristriga has sporadically occurred near the headwaters. The majority coming from the inferior part of the river and near-by affluents. Stomach contents have been analysed according to occurrence frequency and a variety of items has been verified: the most prevailing being the Chironomidae larvae. The feeding activity rhythm has been stablished from crepuscular to nocturnal, with occasional peaks all day over. This analysis defines trophically Pimelodella lateristriga as an carnivorous and benthophagous species. Maturation scales, based on macroscopic and microscopic morphological characteristics, are stablished for males and females. For males, four stages have been defined: young, maturing, mature and semiexhausted. For females five stages have been found: young, maturing, mature, semi-spawned and recovered. It has been observed that the females have bigger length and reach their first sexual maturation with a higher standard length than the males. It has been verified a multiple spawning and a continuous reproductive period, with occurrence of mature individuals all year over.